Risk assessment of construction projects - Zavadskas, Edmundas Kazimieras; Turskis, Zenonas; Tamošaitienė, Jolanta (Journal of Civil Engineering and Management, 2010)
The paper presents risk assessment of construction projects. The assessment is based on the multi‐attribute decision‐making methods. The risk evaluation attributes are selected taking into consideration the interests and goals of the stakeholders as well as factors that have influence on the construction process efficiency and real estate value. Ranking of objects and determination of their optimality are determined by applying TOPSIS grey and COPRAS‐G methods with attributes values determined at intervals. A background and a description of the proposed model are provided and key findings of the analysis are presented. First Published Online: 14 Oct 2010